Temperature Stress Induced Antioxidative and Biochemical Changes in Wheat (Triticum aestivum L.) Cultivars - Sarkar, Jayanwita; Chakraborty, Bishwanath; Chakraborty, Usha (Journal of Plant Stress Physiology, 2016)
The aim of this study is to understand the effect of elevated temperature on wheat seedlings of four cultivars, Gayetri (GY), Gandhari (GN), Kedar (KD), PBW343 in terms of Â tolerance/susceptibility , along with antioxidative and biochemical responses. For this, seedlings of four cultivars were exposed to different temperatures ranging from 25-400C for six hours. According to heat susceptibility index calculated GN was found to be heat tolerant, PBW343 heat sensitive and the other two, GY and KD moderately tolerant.Â  Exposure to high temperature led to gradual increase in membrane lipid peroxidation and hydrogen peroxide accumulation. H2O2 and malonaldehyde accumulated to much higher amount in leaf tissues of PBW343 and GY than GN and KD. Among antioxidative enzymes, catalase, glutathione reductase and ascorbate peroxidase activity initially increased at 350C, followed by reduced activity under heat stress in all cultivars. However, peroxidase activity continued to increase under heat stress. Total chlorophyll and non enzymatic antioxidant carotenoids, initially increased upto 300C, following which there was gradual decrease in these components. Compatible osmolytes - proline and total sugar level within cellular compartments were enhanced upto 350C. Results suggested that wheat can endure heat induced oxidative stress up to certain period, manifested by elevation of non enzymatic antioxidants and osmo protectants, as well as upregulation of antioxidative enzymes.